Do School Ties Matter? Evidence from the Promotion of Public Prosecutors in Korea - Kim, Hyosun; Kim, Tae Jong; Lee, Minkyu (KDI School of Public Policy and Management, 2005)
Does stronger networks capital favor graduates from elite schools over their same-ability peers in promotion? To help answer the question, we examine the public prosecutors' position changes data in South Korea. The key empirical challenge is to control for unobserved individual heterogeneity, such as ability. For the purpose, we employ various techniques such as shared frailty model in duration analysis, instrumental variables estimation, and panel fixed effects estimation. Once we control for individual heterogeneity, the apparent effects of school ties largely disappear. Even when we take OLS evidence at face value, which does not account for unobserved heterogeneity, favoritism based on school ties seems to be a phenomenon limited to the highest echelon of the hierarchy.
Keywords: labor markets; credentialism; discrimination